Beauty for All: Tata Rias Wajah dan Strategi Pemasaran Berbasis Teknologi untuk Penyandang Disabilitas - Maghfiroh, Anik; Ihsani, Ade Novi Nurul; Setyowati, Erna; Afifah, Indah Indi; Sudarni, Ajeng Rahma; Tumangger, Mia Hafizah (Jurnal Abdimas, 2025)
The main problems faced by people with disabilities in roemah difabel semarang are the lack of knowledge and skills in applying makeup, limited access to skills education, and economic difficulties. This problem is the main reason for the implementation of this community service activity, with the aim of creating a more productive and sustainable life. This activity aims to provide comprehensive training to people with disabilities in roemah difabel, so that they can understand and apply the right techniques in doing makeup. The methods chosen to implement this community service are as follows: 1) lectures and questions and answers are used when providing material about makeup and technology, 2). practical methods are used when the resource person or speaker practices the steps in applying makeup, then the trainees are asked to practice applying makeup that has been practiced by the resource person with guidance from the resource person and students of the community service team. 3) monitoring and evaluation to assess participants' understanding and skills. The results of this activity ran smoothly and without obstacles, with the enthusiasm of persons with disabilities reflecting increased knowledge and skills in applying makeup. This activity succeeded in improving the quality of makeup according to appropriate techniques, thus having a positive impact on the training participants.